2022
DOI: 10.3390/healthcare10071294
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Level and Factors Influencing Emergency Department Nurses Fatigue: A Case Study of the Saudi Arabian Context

Abstract: Background: Work-related fatigue is a common health problem among nurses which can affect their performance and decision making. Significance and Aim: The study explores the levels of fatigue and its associated factors among emergency department (ED) nurses in Saudi Arabia. Methods: The study was developed through a cross-sectional quantitative study design. This included the collection of primary quantitative data with a questionnaire prepared and published on REDCap. The study questionnaire was adapted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…In literature, other studies have previously found that nurses working in the ED had higher levels of physical fatigue and psychological exhaustion compared with nurses in the nephrology department, the oncology department, and the intensive care unit (Alshammari, AlEnazy, Alshammari, Madkhali, & Al-Masaeed, 2022). In our study, ED nurses rated OF at moderate levels, opposite to the finding of Jathanna and D'Silva (2014), in which ED nurses had a high score of OF.…”
Section: Discussioncontrasting
confidence: 99%
“…In literature, other studies have previously found that nurses working in the ED had higher levels of physical fatigue and psychological exhaustion compared with nurses in the nephrology department, the oncology department, and the intensive care unit (Alshammari, AlEnazy, Alshammari, Madkhali, & Al-Masaeed, 2022). In our study, ED nurses rated OF at moderate levels, opposite to the finding of Jathanna and D'Silva (2014), in which ED nurses had a high score of OF.…”
Section: Discussioncontrasting
confidence: 99%
“…The result showed that CO 2 level at 1000 ppm was associated with a reduction in the decision-making performance. The reduction of decision-making performance was reported to be influenced by fatigue [23] and drowsiness [24]. These findings may suggest that the relationship between CO 2 exposure and drowsiness is biologically plausible.…”
Section: Discussionmentioning
confidence: 91%
“…The issue of work-related fatigue is prevalent among nurses, as evidenced by a survey conducted in Saudi Arabia among emergency department nurses revealing a high degree of nursing fatigue [42]. Additionally, during the COVID-19 period, a survey of 1,794 nurses in Wuhan found that one-third of them experienced fatigue [ 43 ]. Hence, it is evident that fatigue is a common problem among medical workers worldwide and warrants attention.…”
Section: Discussionmentioning
confidence: 99%